OPTIMALISASI WAKTU DAN BIAYA PROYEK DENGAN METODE CPM, PERT, DAN CRASHING PROYEK LAPANGAN KONTAINER OLEH PT. SINAR CAKRA ABADI - Wendi Juliansyah, (2022)
Project planning requires supporting aspects so that errors do not occur such as increasing completion time. Delays occur from the influence of weather and workers' needs are not met. This research uses a container field project that takes 147 days. This project has a project time delay of 12 days so that acceleration is needed, the purpose of this research is to identify critical activities, calculate the probability of project success, and determine the optimal time and cost. The research methods are CPM, PERT, and Crashing. The CPM method knows 26 critical activities, then the PERT method knows a 95.35% chance of project success, crashing the addition of 1 hour of overtime work cuts 14 days at a cost of Rp. 7,520,647,067.57, the addition of 2 hours of overtime work cuts 24 days at a cost of Rp. 7,535,950,438.35. The optimal alternative is the addition of 1 hour of overtime work with a cost slope of Rp. Rp. 355,256.82. The application of the CPM, PERT, and crashing methods costs Rp. 7,520,647,067.57 and a penalty if 12 days of extra time costs Rp. 7,554,362,977.69 with a cost difference of Rp. 33,715,910,12.